Efficacy of Arsenicum album 30cH in preventing febrile episodes following DPT-HepB-Polio vaccination − a randomized, double-blind, placebo-controlled clinical trial. (February 2018) - Ghosh, Shubhamoy; Ghosh, Taraknath; Mondal, Ramkumar; Patra, Supratim; Das, Sumantra; Ali, Sk. Swaif; Koley, Munmun; Saha, Subhranil
Abstract: Background: Among the post-immunization adverse events, especially of Diphtheria-Pertusis-Tetanus (DPT), fever is a common systemic reaction. There is anecdotal support for the use of the homeopathic medicine Arsenicum album in preventing post-vaccination fever. The investigators intended to evaluate its efficacy in preventing febrile episodes following vaccination. Methods: In the community medicine out-patient of Mahesh Bhattacharyya Homoeopathic Medical College and Hospital, West Bengal, India, between August 2014 and January 2017, a double-blind, randomized, placebo-controlled trial was conducted on 120 children (verum: 60, placebo: 60) who presented for the 2nd and 3rd dose of DPT-HepB-Polio vaccination and reported febrile episodes following the 1st dose. Intervention used was Arsenicum album 30cH 6 doses or placebo (indistinguishable from verum), thrice daily for two subsequent days. Parents were advised to report any event of febrile attacks within 48 h of vaccination, either directly or over telephone. Results: The groups were comparable at baseline. Children reporting fever after the 2nd dose was 29.8% and 30.4% respectively for the homeopathy group and control group respectively [Relative Risk (RR) = 1.008] with no significant difference ( P  = 0.951) between groups. Again after the 3rd dose, children reporting fever were 31.5% and 28.3% respectively for the homeopathy group and control group respectively (RR = 0.956) with no significant difference ( P  = 0.719) between groups. Conclusion: Empirically selected Arsenicum album 30cH could not produce differentiable effect from placebo in preventing febrile episodes following DPT-HepB-Polio vaccination. [Trial registration: CTRI/2017/02/007939]